(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3bGSGf s)
(3ChdgG (B:s
(3jHOC GdehLhO efgG HeGOI (B" (3YhU (B" (3, Hbhdg (B: (3GYJGU Ydjg GdCeQ Ci GdJhi hGZJGUJ GdfGbI EPG VQHgG GdaMd , hde JMed hdG Ydg HgG hTGI YGFU EPG de JMed CYhGekG s
(3JJab BNQgG eY BNQ fSNI YGQa MceJ(B28 (3dZI HGNJdGa jSjQ ai HYV GdCdaGX CjVGs
(3hbO cJHJ Yf fSNI cJHgG YHjO Gddg GdNGWi GdeQJVi GdLYaQi ai bGSGf CjVkG SfI (B596(3g`s
(3fSNI SGOSI YTQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs